2011
DOI: 10.1007/s10152-011-0277-9
|View full text |Cite
|
Sign up to set email alerts
|

The diatom Mediopyxis helysia Kühn, Hargreaves & Halliger 2006 at Helgoland Roads: a success story?

Abstract: The Helgoland Roads phytoplankton long-term data set is one of the longest and the most detailed data sets in Europe, having provided continuous work-daily observations of phytoplankton abundance since 1962. These high frequency counts have undergone and are continuously subject to a high level of quality control. The Helgoland data set thus is useful in the evaluation of new records in phyto-and zooplankton. Here, we report the Wrst appearance of the relatively recently described diatom Mediopyxis helysia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Over the course of the survey, several phytoplankton taxa have been discovered in areas where they were previously absentMediopyxis spp. (Kraberg et al, 2012), Coscinodiscus wailesii (Boalch and Harbour, 1977;Edwards et al, 2001a), and Neodenticula seminae (Reid et al, 2007). For a number of these taxa, vectors of introduction (e.g.…”
Section: Informing Non-biodiversity Indicators Of Gesmentioning
confidence: 99%
“…Over the course of the survey, several phytoplankton taxa have been discovered in areas where they were previously absentMediopyxis spp. (Kraberg et al, 2012), Coscinodiscus wailesii (Boalch and Harbour, 1977;Edwards et al, 2001a), and Neodenticula seminae (Reid et al, 2007). For a number of these taxa, vectors of introduction (e.g.…”
Section: Informing Non-biodiversity Indicators Of Gesmentioning
confidence: 99%
“…This is a large bipolar centric diatom species (apical diameter up to 100 µm first recorded from the Gulf of Maine and the island of Sylt, see also [19]). It was first recorded at the Helgoland Roads site in March 2009 [20]. The species has characteristic star-shaped chloroplasts and the valve outline, which has one rounded and one pointed valve apex, is also diagnostic.…”
Section: Mediopyxis Helysia Kühn Hargreaves and Halliger 2006 (Figmentioning
confidence: 99%
“…An earlier study reported that this species was first observed in 2003 [21], but it was not observed during the routine phytoplankton counts on Lugol samples, and did not appear in the 2004 check-list. Mediopyxis helysia formed extensive blooms in Helgoland Roads in 2010 (and also in the Dutch Wadden Sea [22], but appears to be restricted to quite specific environmental conditions occurring predominantly during periods with reduced salinities [20] and its numeric importance appears to be diminishing again at least at Helgoland Roads.…”
Section: Mediopyxis Helysia Kühn Hargreaves and Halliger 2006 (Figmentioning
confidence: 99%
“…These media were prepared from filtered natural seawater from the shores of Sylt and additional nutrients which the diatoms need to grow (0.88 mmol NO 3 ) and which is a common used medium as described by Guillard et al (1975) and Kraberg et al (2012). Both cultures were incubated in the F/2 medium at 16 • C with 12 h light-12 h dark cycling (LUMILUX Plus Eco daylight lamp; ca.…”
Section: Experimental Set-upmentioning
confidence: 99%